Literatura e conhecimento - Régis, Sônia (GALÁxIA. Revista Interdisciplinar de Comunicação e Cultura, 2007)
Na acepção dominante, a meta da ciência continua sendo a de ordenar as experiências em sistemas ditos racionais (discursos objetivos) e a da literatura, a de transformálas em razões poéticas (discursos subjetivos), dando continuidade a uma falsa ruptura (surgida no Iluminismo) entre essas duas experiências psíquicas. Nossa proposta é rever essa concepção para devolver à literatura o seu lugar de conhecimento. Palavras-chave ciência, literatura, conhecimento, linguagem. Abstract Under the dominant acception, the goal of science continues to be the ordination of experiences within the so called rational systems (objective discourse). On the other hand the goal of literature is to transform these experiences into poetical reasons (subjective discourse), giving continuity to a false rupture (that came up during Enlightment) between these two psychological experiences. Our proposal is to review this conception in order to give back to literature its place as a producer of knowledge. Key words science, literature, knowledge, language.